2013
DOI: 10.5665/sleep.2370
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sublingual Low-Dose Zolpidem Tablet Reduces Latency to Sleep Onset following Spontaneous Middle-of-the-Night Awakening in Insomnia in a Randomized, Double-Blind, Placebo-Controlled, Outpatient Study

Abstract: NCT00466193: "A Study of Zolpidem Tartrate Tablet in Adult Patients with Insomnia" http://www.clinicaltrials.gov/ct2/show/NCT00466193?spons=%22Transcept+Pharmaceuticals%22&spons_ex=Y&rank=2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 7 publications
0
33
0
1
Order By: Relevance
“…Erman Fourteen additional studies met inclusion criteria but could not be included in meta-analysis due to inadequate data sets. 71,[83][84][85][86][87][88][89][90][91][92][93][94][95] Pertinent results from these studies are noted independently of meta-analysis results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erman Fourteen additional studies met inclusion criteria but could not be included in meta-analysis due to inadequate data sets. 71,[83][84][85][86][87][88][89][90][91][92][93][94][95] Pertinent results from these studies are noted independently of meta-analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…57 [88][89][90]92,94,95 These studies varied significantly with regard to drug preparation, dosage, mode of administration and methodology, rendering comparisons between them or to the meta-analytic data difficult. Four of the six evaluated sublingual zolpidem, primarily for treatment of middle-of-the-night (MOTN) awakenings.…”
Section: Sleep Latencymentioning
confidence: 99%
“…Six studied individual in-person CBT-I, [54][55][56]60,62,65 five studied group CBT-I, 53,57,59,61,72 one studied phonedelivered CBT-I, 51 and ten studied self-help CBT-I using either books or handouts or electronic resources. 52,58,63,64,[66][67][68][69][70][71] Comparison groups also varied across trials. Some trials attempted to have a placebo control group that received similar therapy hours (i.e., quasi-desensitization or stress management).…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…Double blind study and with a low attrition rate. Roth 2013; 69 Roth 2014 70 Low Adjusted for multiple comparisons using hierarchy; 20/294 (7%) attrition; reporting bias, i.e., data only for TST; outcomes for NOW, SL must be estimated from figure; no data for WASO Herring 2014; 71 Herring 2012 72 Low. Computer-generated randomization schedule based on input from a blinded Merck statistician.…”
Section: Appendix a Search Strategies Key Question Trials Searches -mentioning
confidence: 99%
“…45 However, effect sizes for improvements in daytime functioning, including alertness, ability to concentrate and to function, and physical well-being, were modest for all groups, although highest in groups with primary insomnia and lowest in those with comorbid psychiatric conditions. Roth et al 46 examined sublingual low-dose zolpidem (3.5 mg) for patients with primary insomnia and difficulty returning to sleep after nighttime awakenings (N = 295). Results showed that, compared with placebo, this formulation significantly decreased sleep latency (P < .0001) and favored zolpidem in ratings of morning sleepiness/alertness (P = .004).…”
Section: Fda-approved Prescription Medications For Insomniamentioning
confidence: 99%